Clinical Significance of Indeterminate QuantiFERON-TB Gold Plus Assay Results in Hospitalized COVID-19 Patients with Severe Hyperinflammatory Syndrome - Solanich, Xavier (J Clin Med, 2021)
Performance of the QuantiFERON-TB Gold Plus (QFT-Plus) assay could be affected by conditions of immune dysregulation. Little is known about the reliability of QTF-Plus in COVID-19 patients. Our aim was to determine the prevalence and the factors related to an indeterminate QFT-Plus test in COVID-19 hospitalized patients, and to analyze its relationship with in-hospital mortality. A retrospective analysis of all hospitalized COVID-19 patients on whom a QTF-Plus assay was performed in a tertiary care public hospital during the first epidemic wave in Spain (March–April 2020). Out of a total of 96 patients included, 34 (35.4%) had an indeterminate result, in all cases due to a lack of response in the mitogen control. Factors related to COVID-19 severity, such as higher lactate dehydrogenase (LDH) (odds ratio [OR] 1.005 [95% confidence interval [CI] 1.002–1.008]) and previous administration of corticosteroids (OR 4.477 [95% CI 1.397–14.345]), were independent predictors for indeterminate QFT-Plus assay. Furthermore, indeterminate results were more frequent among COVID-19 patients who died during hospitalization (29.1% vs. 64.7%; p = 0.005). We conclude that QFT-Plus assay yielded an unexpected, high prevalence of indeterminate results in severe COVID-19 patients. Factors related to worse COVID-19 outcome, such as LDH, as well as corticosteroid use before the QFT-Plus assay, seem to be predictors for an indeterminate result. The role of an indeterminate QFT-Plus result in predicting COVID-19 severity and mortality should be evaluated.